Web usability test in 60 seconds: a theoretical foundation and empirical test - Imran Mahmud; Mostafijur Rahman; Sharmin Ahmed; Didarul Islam (Institute of Advanced Engineering and Science, 2020)
The aim of this research is to explore the possibility of web usability test in 60 seconds rather than unlimited time by customers. Usability was tested by two major testing methods: system usability scale (SUS) and NetQu@l. 60 customers as two groups were involved in the experimental design procedure. The assessment included an online shopping website where one group tested in 60 seconds and other group had 3 days to test. Result shows that there are significance differences in SUS based testing and no significant differences in NetQu@l based testing. Altogether, these results provide further support that SUS based usability testing can be implemented in 60 seconds time frame without imposing additional cognitive load on customers.